Voice onset time of Mankiyali language: an acoustic analysis - Ullah, Shakir; Anjum, Uzma; Saleem, Tahir (Penerbit Universiti Kebangsaan Malaysia, 2023)
The endangered Indo-Aryan language Mankiyali, spoken in northern Pakistan, lacks linguistic documentation and necessitates research. This study explores the Voice Onset Time (VOT) values of Mankiyali's stop consonants to determine the duration of sound release, characterized as negative, positive, and zero VOTs. The investigation aims to identify the laryngeal categories present in the language. Using a mixed methods approach, data were collected from five native male speakers via the Zoom H6 platform. The study employed the theoretical framework of Fant's (1970) source filter model and analyzed each phoneme using PRAAT software. Twenty-five tokens of a single phoneme were recorded across the five speakers. The results reveal that Mankiyali encompasses three laryngeal categories: voiceless unaspirated (VLUA) stops, voiceless aspirated (VLA) stops, and voiced unaspirated (VDUA) stops. The study highlights significant differences in VOTs based on place of articulation and phonation. In terms of phonation, the VLUA bilabial stop /p/, alveolar stop /t/, and velar stop /k/ exhibit shorter voicing lag compared to their VLA counterparts /pʰ, tʰ, kʰ/. All VLUA and VLA stops display +VOT values, while all VDUA stops exhibit -VOT values. Regarding place of articulation, the bilabial /p/ demonstrates a longer voicing lag than the alveolar /t/ but a shorter lag than the velar /k/. Additionally, the results indicate similarities in voicing lag among the VDUA stops /b, d, ց/. This study offers valuable insights into the phonetic and phonological aspects of Mankiyali and holds potential significance for the language's preservation.